2010
DOI: 10.1088/0022-3727/43/49/495202
|View full text |Cite
|
Sign up to set email alerts
|

Plasma diagnostics and device properties of AlGaN/GaN HEMT passivated with SiN deposited by plasma-enhanced chemical vapour deposition

Abstract: In this work, silicon nitride thin films have been deposited by Plasma Enhanced Chemical Vapour Deposition (PECVD) on both silicon samples and AlGaN/GaN High Electron Mobility Transistors (HEMT) grown on sapphire substrates. Commercial parallel-plate RF plasma equipment has been used. During depositions, the dissociation rates of SiH 4 and NH 3 precursors and the formation of H 2 and N 2 have been analysed by mass spectrometry as a function of the NH 3 /SiH 4 flow ratio and the RF power applied to the plasma r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…[20][21][22][23] These works exemplify the complexity of the chemistry involved in film deposition and the necessity of getting further insight into the underlying mechanisms, since the properties of the films are correlated with the plasma composition and conditions 20 and have effects on the properties of the devices where these films are deposited. 24 In nuclear fusion research, the interest is focused on the inhibition of film deposition. 25 High fluxes of hydrogen isotopes produce chemical sputtering of carbon-based materials, which leads to the formation of re-deposited (a-C:H) carbon films in regions not directly exposed to plasma.…”
Section: And 6 and References Therein)mentioning
confidence: 99%
“…[20][21][22][23] These works exemplify the complexity of the chemistry involved in film deposition and the necessity of getting further insight into the underlying mechanisms, since the properties of the films are correlated with the plasma composition and conditions 20 and have effects on the properties of the devices where these films are deposited. 24 In nuclear fusion research, the interest is focused on the inhibition of film deposition. 25 High fluxes of hydrogen isotopes produce chemical sputtering of carbon-based materials, which leads to the formation of re-deposited (a-C:H) carbon films in regions not directly exposed to plasma.…”
Section: And 6 and References Therein)mentioning
confidence: 99%
“…It is found that the interface trap states are greatly suppressed. SiN x has almost twice dielectric constant to SiO 2 , excellent thermal stability, and electronic insulating properties, which has been utilized in the AlGaN/GaN HEMT MISFETs to reduce interface state density and increase threshold voltage stability [12][13][14]. By introducing SiN x as the gate dielectric for p-GaN MIS capacitor, a high-quality and highly stable interface with low-density interface states and trapping states was developed with an effective two-step surface treatments from both electrical and microstructural invest igation.…”
Section: Introductionmentioning
confidence: 99%
“…When SiN layer has a dense structure, hydrogen from the SiN film cannot be able to diffuse through the film and replace the lost hydrogen at the interface. Garcia et al [11] and Romero et al [12] found a linear relationship between the N-H bond density and the minimum interface trap density (D it ). A large proportion of works focus on the effect of SiN film composition on the passivation characteristic of metal/SiN/Si structure and scarce research [13,14] on the Schottky characteristic in GaN HEMTs with SiN layer.…”
Section: Introductionmentioning
confidence: 99%